Excess Postexercise Oxygen Consumption and Fat Utilization Following Submaximal Continuous and Supramaximal Interval Running. Issue 4 (2nd October 2018) - Islam, Hashim; Townsend, Logan K.; Hazell, Tom J.
ABSTRACT: Purpose : Few studies have directly compared excess postexercise oxygen consumption (EPOC) and fat utilization following different exercise intensities, and the effect of continuous exercise exceeding 75% of maximal oxygen uptake (VO2 max) on these parameters remains unexplored. The current study examined EPOC and fat utilization following acute moderate- and vigorous-intensity continuous training (MICT and VICT) and sprint interval training (SIT).Methods : Eight active young men performed 4 experimental sessions: (a) MICT (30 min of running at 65% VO2 max); (b) VICT (30 min of running at 85% VO2 max); (c) SIT (4 30-s "all-out" sprints with 4 min of rest); and (d) no exercise (REST). Excess postexercise oxygen consumption and fat oxidation were estimated from gas measurements (VO2 and carbon dioxide production [VCO2 ]) obtained during a 2-hr postexercise period.Results : Total EPOC was similar ( p  = .097; effect size [ES] = 0.3) after VICT (8.6 ± 4.7 L) and SIT (10.0 ± 4.2 L) and greater after both (VICT, p  = .025, ES = 0.3, and SIT, p  < .001, ES = 0.6) versus MICT (6.0 ± 4.3 L). Fat utilization increased after MICT (0.047 ± 0.018 g· min −1, p  = .018, ES = 1.3), VICT (0.066 ± 0.020 gmin −1, p  = .034, ES = 2.2), and SIT (0.115 ± 0.026 gmin −1, p  < .001, ES = 4.0) versus REST (0.025 ± 0.018 gmin −1 ) and was greatest after SIT ( p  < .001, ES = 3.0 vs. MICT; p  = .031, ES = 2.1 vs. VICT).Conclusion : Acute exercise increases EPOC and fat utilization in an intensity-dependent manner.